Evaluation of Antimicrobial, Thrombolytic and CNS-Depressant Activities of Three Medicinal Plants Available in Bangladesh - Tabassum, Fatema; Akther Akhi, Amena; Akter Chumki, Mukta; Rahman, Lioyaja; Imran Nur Manik, Md. (Asian Journal of Chemistry, 2021)
The aim of the present study was to explore antimicrobial, thrombolytic and CNS-depressant activity of three medicinal plants Plumbago zeylanica, Trewia nudiflora and Aphanamixis polystachya available in Bangladesh. At room temperature, the plant parts were subjected to cold extraction with methanol, giving rise to concentrated methanolic extracts (MEF) followed by fractionation applying revised Kupchan partitioning procedure to obtain different soluble fractions namely to hexene fraction (HXF), ethyl acetate fraction (EAF), chloroform fraction (CLF) and aqueous fraction (AQF). To study the antimicrobial activity of these fractions, the disc diffusion method was used, where kenamycin was used as standard. Thrombolytic potential was determined by investigating clot rupture (% clot lysis) for this purpose streptokinase was employed as the positive control whereas water was the negative control. For the evaluation of CNS depressant activity, the open-field method was utilized and diazepam was chosen as the reference standard. Among the three plants, the crude methanolic fraction of P. zeylanica demonstrated good antimicrobial action over the majority of the bacterial strains assayed and the crude methanolic extract exhibited the maximum antimicrobial activity against S. aeruginosa (zone of inhibition was 23.46 ± 2.19 mm). The chloroform fraction of T. nudiflora showed the highest thrombolytic activity (43.45 ± 2.12% clot lysis). It was observed that the four extracts from the plants under investigation had CNS depressant activity. Particularly, the aqueous fraction of P. zeylanica (12.00 ± 0.913); n-hexane fraction of T. nudiflora (09.75±0.854) and A. polystachya (08.50 ± 0.645) demonstrated consistently significant CNS depressant activity, in terms of the number of squares crossed at 120 min; producing a prominent decrease in the measurement of movement.